Kerjasama Pengelolaan Perbatasan Indonesia–Malaysia: Prospek dalam Mewujudkan Kawasan Perbatasan yang Aman dan Sejahtera - Ridwan Maulana; Christoforus Arel S. Heuk; Yusa Djuyandi (PT. Data Jaringan Visual Indonesia (Djava), 2026)
Border areas are a strategic manifestation of territorial sovereignty for national integrity and natural resource management. However, these regions often face complex challenges regarding human security, such as poverty and food insecurity. This research aims to explore the dynamics of bilateral cooperation between Indonesia and Malaysia in realizing a secure and prosperous border, focusing on the land territory of Kalimantan as well as the maritime regions of the Malacca Strait and the Celebes Sea. Using a qualitative descriptive-analytical approach with a case study method, this research relies on secondary data from policy documents and academic literature. The research results identify five main dimensions of cooperation: territorial boundary affirmation, security (joint patrols), economy (revitalization of State Border Posts), social-labor relations, and environmental protection. Although institutional cooperation has been established, its effectiveness is hindered by maritime delimitation disputes, economic development disparities, the prevalence of illegal activities through